Transcranial cortico-cortical paired associative stimulation (ccPAS) over ventral premotor-motor pathways enhances action performance and corticomotor excitability in young adults more than in elderly adults - Turrini, Sonia; Bevacqua, Naomi; Cataneo, Antonio; Chiappini, Emilio; Fiori, Francesca; Candidi, Matteo; Avenanti, Alessio (Frontiers in Aging Neuroscience, 2023)
Transcranial magnetic stimulation (TMS) methods such as cortico-cortical Paired Associative Stimulation (ccPAS) can increase the strength of functional connectivity between ventral premotor (PMv) and primary motor cortex (M1) via spike-timing-dependent-plasticity (STDP), leading to enhanced motor functions in young adults. However, whether such STDP-inducing protocol is effective in the aging brain remains unclear. In two groups of young and elderly healthy adults, we evaluated manual dexterity with the 9-hole peg task before and after the administration of left PMv-M1 circuit ccPAS. We observed that ccPAS enhanced dexterity in young adults, anticipated by a progressive increase in motor-evoked potentials (MEPs) during protocol administration. No similar effects were observed in elderly individuals or in a control task. Across age groups, we observed that the magnitude of MEP changes predicted larger behavioral improvements. These findings demonstrate that left PMv-to-M1 ccPAS induces functionally specific improvements in young individuals’ manual dexterity along with an increase in corticomotor excitability, while altered plasticity prevents ccPAS effectiveness in the elderly.